PERANCANGAN SISTEM INFORMASI MONITORINGHASIL PERKEMBANGAN BELAJAR PADA KELOMPOKBERMAIN AULIA AL - KAMIL BERBASIS WEBSITE - Rahadyan Pandu Admara, (2022)
The Aulia Al - Kamil Family Planning Foundation is a play group that has learning rules accompanied by playing activities or commonly called playing while learning. The system for processing and delivering data related to information is still by distributing brochures. Parents of students have not been able to know the value of children's development because they have to wait until the end of the semester. The problem is designing information websites, school activities, websites as a means to monitor children's development activities. The purpose of is research is an information system that will be able to provide and deliver school profile information as well as information on learning activities at foundations, profiles and values of children's development results and can conduct PPDB online through the website. This methodology uses the Waterfall method which has a process flowing from one stage to another gradually moving in a downward fashion. This study resulted in a web-based information system for monitoring learning outcomes using the PHP language and using the Codeigniter framework which has online PPDB features, features viewing school information, viewing teacher information, information features on learning progress scores and payment information features made by parents.